2016
DOI: 10.1038/onc.2016.247
|View full text |Cite
|
Sign up to set email alerts
|

FBW7 mutations mediate resistance of colorectal cancer to targeted therapies by blocking Mcl-1 degradation

Abstract: Colorectal cancer (CRC), the second leading cause of cancer-related deaths in the US, has been treated with targeted therapies. However, the mechanisms of differential responses and resistance of CRCs to targeted therapies are not well understood. In this study, we found that genetic alterations of FBW7, an E3 ubiquitin ligase and a tumor suppressor frequently mutated in CRCs, contribute to resistance to targeted therapies. CRC cells containing FBW7 inactivating mutations are insensitive to clinically used mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 48 publications
4
146
0
Order By: Relevance
“…Equivalent quantities of RNA underwent reverse transcription in order to generate cDNA with the help of random hexamers, as well as the TaqMan miRNA reverse transcription kit (Applied Biosystems, Foster City, CA, USA) [26]. SYBR Green Real time PCR Master Mix (Toyobo, Osaka, Japan) was used for quantitative real-time PCR.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…Equivalent quantities of RNA underwent reverse transcription in order to generate cDNA with the help of random hexamers, as well as the TaqMan miRNA reverse transcription kit (Applied Biosystems, Foster City, CA, USA) [26]. SYBR Green Real time PCR Master Mix (Toyobo, Osaka, Japan) was used for quantitative real-time PCR.…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…PTEN loss is a commonly seen genetic variation in cancers like, gastric cancer, breast cancer, and spongioblastoma 26, 27. It is closely connected with cytotoxic drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings elucidate a critical functional role of FBW7 mutations and Mcl-1 stability in differential sensitivity and resistance of CRC cells to Hsp90 inhibition. Most of the FBW7 mutations in CRCs are heterozygous point mutations (29). Mutant FBW7 may have altered protein stability, or act as dominant negative proteins upon hetero-dimerization with WT FBW7 (23).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by us and other groups showed that p53 mutational status influences 17-AAG sensitivity through the effects on p53 downstream targets including PUMA, Bax, Bim, and p21 (13ā€“15). Our recent study showed that colon cancer cells contain a small fraction (~0.1%) of pre-existing FWB7 -mutant cells, which can be enriched upon treatment with the multi-kinase inhibitor regorafenib, leading to acquired drug resistance (29). It is possible that these cells can also escape from death induced by Hsp90 inhibitors and cause acquired resistance to these agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation